Behavioral Correlates of GPS Device Usage Among Small-Scale Fishers in Malaysia. (March 2021) - Mohamed Shaffril, Hayrol Azril; Eric Krauss, Steven; Hamzah, Azimi; Abu Samah, Bahaman
This article aims to examine the relationship between selected behavioral factors and Global Positioning System (GPS) usage among small-scale fishers in Malaysia. An adapted version of the Unified Theory of Acceptance and Use of Technology (UTAUT) was tested among a sample of 400 small-scale fishers to examine the relationship between technology-related behavioral constructs (compatibility, social influence, effort expectancy, learning culture, and performance expectancy) and GPS usage. The sample was selected from 12 fishery districts in Malaysia. Confirmatory factor analysis (CFA) confirmed that all five technology-related behavioral constructs included in the model recorded a significant relationship with GPS usage. The results extend the generalizability of the UTAUT to a previously understudied setting of community technology usage. Understanding GPS usage among small-scale fishers from the extended UTAUT perspective can provide policy makers, public, nongovernmental organizations (NGOs), and other concerned parties with knowledge that can build awareness and shape capacity building efforts for small-scale interventions to increase the use of GPS. This will, in turn, reduce the risks associated with fishing routines and enhance fishing yields.